Sparganosis: A rare case of the oral cavity - Iamaroon A. (2014)
Sparganosis is a rare parasitic disease. We here reported an extremely rare case of intraoral sparganosis in a 21-year-old Thai female. Clinically, the lesion presented as an asymptomatic nodule 1cm × 1cm in the left upper labial mucosa. An excisional biopsy was performed and the pathological examinations revealed a larva of a sparganum surrounded by a fibrous capsule heavily infiltrated with eosinophils. Excision of the lesion was curative. The possible route of infection of the patient might be due to drinking water, contaminated with Cyclops containing procercoid larvae.